A novel accurate LC-MS/MS method for quantitative determination of Z-lumirubin - Jašprová, Jana; Dvořák, Aleš; Vecka, Marek; Leníček, Martin; Lacina, Ondřej; Valášková, Petra; Zapadlo, Miloš; Plavka, Richard; Klán, Petr; Vítek, Libor (Scientific reports, 2020)
Although phototherapy (PT) is a standard treatment for neonatal jaundice, no validated clinical methods for determination of bilirubin phototherapy products are available. Thus, the aim of our study was to establish a such method for clinical use. To achieve this aim, a LC-MS/MS assay for simultaneous determination of Z-lumirubin (LR) and unconjugated bilirubin (UCB) was conducted. LR was purified after irradiation of UCB at 460 nm. The assay was tested on human sera from PT-treated neonates. Samples were separated on a HPLC system with a triple quadrupole mass spectrometer detector. The instrument response was linear up to 5.8 and 23.4 mg/dL for LR and UCB, respectively, with submicromolar limits of detection and validity parameters relevant for use in clinical medicine. Exposure of newborns to PT raised serum LR concentrations three-fold (p < 0.01), but the absolute concentrations were low (0.37 ± 0.16 mg/dL), despite a dramatic decrease of serum UCB concentrations (13.6 ± 2.2 vs. 10.3 ± 3.3 mg/dL, p < 0.01). A LC-MS/MS method for the simultaneous determination of LR and UCB in human serum was established and validated for clinical use. This method should help to monitor neonates on PT, as well as to improve our understanding of both the kinetics and biology of bilirubin phototherapy products.
Keywords: Phototherapy; novorozenecká žloutenka; molekulární struktura; Infant, Newborn; Serum; bilirubin; sérum; tandemová hmotnostní spektrometrie; Bilirubin; novorozenec; Humans; Chromatography, Liquid; Tandem Mass Spectrometry; fototerapie; chromatografie kapalinová; Jaundice, Neonatal; lidé; Molecular Structure